Adaptation of Variety Diversity on Growth and Production in the Area of Onion Plant Marginals (Allium ascalanicum L.) - Upe, Ambo; Sau, Tenri (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study aims to obtain variety with broad adaptations that are able to grow and produce optimal production on marginal fields of onion planting, which can improve farmers' welfare, reduce dependence on red onion imports, become exporters of onion to food sovereignty. The method that will be used is a Randomized Block Design (RBD) method consisting of five red onion variety as treatment, namely BimaBrebes, Tajuk, Bauji, Super Philip, and Local Enrekang variety. Each treatment was repeated three times. Data processing with SPSS Software, Version 22, and if there is a real influence, then a different test is performed with the Duncan Test at the level of ap= 0.05. The research was carried out on the experimental land of STIP PuangrimaggalatungSengkang. The parameters observed consist of the growth and production of onion plants. The results of the analysis showed that the onion variety that was quite adaptive was BimaBrebes variety onion and was able to produce an average production of 12.08 t ha-1.